2023
DOI: 10.1111/jcms.13557
|View full text |Cite
|
Sign up to set email alerts
|

Equal Focus on Inequality? Approaches to Distributional Impact Assessment in the National Budget Process Across the EU

Nicola Bazoli,
Carlo Fiorio,
Sonia Marzadro
et al.

Abstract: After four decades of increasing within‐country income inequality in many EU Member States, this study first aims to understand to what extent and how EU Member States make use of distributional impact assessments (DIAs) for budgetary measures. The second aim is to understand the factors that constrain the use of DIA, leading us to propose strategies for how it could be used more widely. To these ends, we perform a desk‐based study of the documents produced in the national budgeting process, which is then foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The estimates of the average learning loss in reading and mathematics presented in this study are in line with the findings reported by Borgonovi and Ferrara (2023) and Bazoli et al. (2022) , who observe a more severe learning loss for grade-8 students than for grade-5 students, when present.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The estimates of the average learning loss in reading and mathematics presented in this study are in line with the findings reported by Borgonovi and Ferrara (2023) and Bazoli et al. (2022) , who observe a more severe learning loss for grade-8 students than for grade-5 students, when present.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, previously middle performers are those who suffered the most the Covid-19 impact. The baseline results are confirmed by Bazoli et al. (2022) , who estimate the magnitude of the learning loss for grades 5, 8 and 13.…”
Section: Academic Backgroundmentioning
confidence: 57%